Principles of surgery everything you need to know but were frightened to ask! - Andrews, Sam; Cascarini, Luke (Tfm Pub., 2008)
Originally designed for junior surgeons with the College of Surgeons' examinations in mind, [this book] is, in fact, essential knowledge on the principles of surgery and operating theatre practice for all healthcare professionals with an interest in surgery.